The osmotic action of sugar combined with hydrogen peroxide and bee-derived antibacterial peptide Defensin-1 is crucial for the antibiofilm activity of eucalyptus honey. (January 2021) - Proaño, Adrián; Coello, Dayana; Villacrés-Granda, Irina; Ballesteros, Isabel; Debut, Alexis; Vizuete, Karla; Brenciani, Andrea; Álvarez-Suarez, José M.
Abstract: Honey is known for its important antimicrobial activity, which is considered one of its main biological properties. This property has been associated with different factors, among which floral origin stands out and can directly affect this biological activity. The aim of this study was to evaluate the antibiofilm activity of eucalyptus honey (EH) against two multiresistant human pathogens Staphylococcus aureus MRSA S21 and Pseudomonas aeruginosa P28, as well as to investigate the role of several honey components in its antibiofilm action. We also explored the activity of the enzyme glucose oxidase (GOX ), hydrogen peroxide (H2 O2 ) content, and the presence of the antimicrobial peptide bee defensin-1 (Def-1). EH was efficient in inhibiting biofilm formation and removing preformed biofilms. This activity was markedly affected after treatment with catalase and proteinase K, suggesting that antibiofilm activity is related to the presence of H2 O2 and Def-1. Structural changes induced by the osmotic effect of honey sugar was evidenced by scanning electron microscopy, suggesting that EH's antibiofilm capacity is not dependent solely on H2 O2 content or the presence of Def-1. Highlights: Eucalyptus honey (EH) inhibits biofilm formation of multidrug resistant bacteria. EH removes preformed biofilms of multidrug resistant bacteria. The osmotic action, H2 O2 and Def-1 play important roles in antibiofilm activity. The antibiofilm activity of EH is retained after removal of Def-1 and H2 O2 . The osmotic effect causes alteration of bacterial morphology.